PENDEKATAN STUDI MAKRO DALAM PERENCANAAN WILAYAH - -, WIDHIANTINI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 1 Februari 2008, 2012)
The goal of this macro study is preparing an integrated development planning for a regency. The specific goals are to identify and analyze potential, problem, and need in the regency; and to recommend programs needed by the people to make a sustainable development comes true. Macro study approach is a scientific method combining rational method based on the review of previous studies by government agencies with empirical method using survey technique. Data collected include primary and secondary. Secondary data an gained from many institutions, and primary data are collected using observation and interview methods. Bali area has no natural resources like forest, mining, petroleum and coal that give income for the region or government. Therefore, the review of this macro study is very relevant in developing a region, especially rural area based on its strengths, example Karangasem Regency. The reason to choose Karangasem Regency are as follows (1) Karangasem Regency is an area of agricultural commodity and (2) based on the Act No.24/1992, Karangasem Regency is located in quadrant III, i.e., rural corporate area supported by tourism area. The result of study indicated that: (1) potentials of this regency are: (a) laborer adsorbed in agricultural sector is 75,62%, (b) high productive age is 70%, (c) high entrepreneurship of villagers, (d) more than 50% of women are working in small industry, (e) the existence of written and oral regulation from subak and customary village institution, and (f) life principle which is still attached on Balinese (Tri Hita Karana). Problem of this regency are: (a) high input price, (b) limited of land, capital, marketing, and technology, (c) unpredictable price fluctuation and season of agricultural products, (d) low access to continue high school and courses due to limited facility, (e) low treatment skill of volunteer, and (f) limited local government finance. The needs of this regency are: (a) guarantee of agricultural product price, (b) market that can collect all production yield, (c) support and capital assistance from government or private to expand UKM, (d) skill training and capital assistance from local government for small industry, (e) finance assistance from foreigner for regional development, and (f) multi way and coordination among the local people (custom village) and government coordinators.
Keywords: Regional Planning, Potentials, Problems, Needs, Scenario Analysis, Program Format